Interfaith Dialogue and Conflict Transformation in Indonesia - Muhammad Khoirul Muqtafa (Jurnal Identitas, 2025)
Conflicts involving inter-religious groups, both those from the same tradition and those from different traditions, frequently occur in Indonesia. This is evident in various studies conducted by institutions addressing this issue, such as Human Rights Watch, the Setara Institute, and the Wahid Institute. Meanwhile, interreligious dialogue is frequently held in various forums and venues, involving numerous actors. This indicates that the dialogue has not been able to foster a transformation of the existing conflict. Through a literature review, this paper finds that the dialogue demonstrates a lack of commitment from religious leaders, remains highly elitist, and only seeks common ground without discussing and understanding existing differences.